Exchange Rate Fluctuations and Change in Inflation Rates and its Impact on Economic Growth in Iraq for the Period (2010-2024) - Ayyed Jasym Abbood; Yusra Rasim Jabbar (Harmoni Economics: International Journal of Economics and Accounting, 2025)
The research aims to show the impact of exchange rate fluctuations and changes in inflation rates on economic growth, in terms of the impact of the increase in the amount of goods and services produced by a particular economy. The primary components of production—land, labor, capital, and organization—are used to create these things. Furthermore, the rise in the market value of the products and services generated by an economy over time is known as economic growth. As well as the impact on achieving a high growth rate of real per capita income during a certain period of time. Spatial boundaries were represented in the data published by the Central Bank - Directorate General of Statistics and Research. The time limits of the research were a continuous time series of fifteen years from (2010-2022) due to the availability of information and data on the variables of searching for the studied variables. The research reached several conclusions, the most important of which was that exchange rate fluctuations and change in inflation rates can affect the increase in real income and thusaffect the livelihood of citizens and purposeful stability, through which societies are upgraded, as well as the impact on national income, planning, providing the necessary data and information, production of quality, providing appropriate technology and developing appropriate economic policies.